Is there any place for LDR brachytherapy for head and neck carcinomas in HDR era? - Fijuth, Jacek (J Contemp Brachytherapy, 2009)
In Poland, the classical LDR brachytherapy for head and neck carcinomas with Ir-192 wires or hairpins has completely disappeared some time ago after 30 years of successful clinical use. Can this technique be fully and safely replaced by HDR or PDR application? This option seems attractive because of new possibilities of 3D reconstruction and computer real-time treatment planning and optimization. However, in my opinion, long time is needed to get a clinical and scientific experience that has been accumulated for decades with the use of LDR technique.